Different Aspects of Classical Pathway Overactivation in Patients With C3 Glomerulopathy and Immune Complex-Mediated Membranoproliferative Glomerulonephritis - Michels, Marloes A. H. M.; van de Kar, Nicole C. A. J.; van Kraaij, Sanne A. W.; Sarlea, Sebastian A.; Gracchi, Valentina; Engels, Flore A. P. T.; Dorresteijn, Eiske M.; van der Deure, Johannes; Duineveld, Caroline; Wetzels, Jack F. M.; van den Heuvel, Lambertus P. W. J.; Volokhina, Elena B. (Frontiers in Immunology, 2021)
The rare and heterogeneous kidney disorder C3 glomerulopathy (C3G) is characterized by dysregulation of the alternative pathway (AP) of the complement system. C3G is often associated with autoantibodies stabilizing the AP C3 convertase named C3 nephritic factors (C3NeF). The role of classical pathway (CP) convertase stabilization in C3G and related diseases such as immune complex-mediated membranoproliferative glomerulonephritis (IC-MPGN) remains largely unknown. Here, we investigated the CP convertase activity in patients with C3G and IC-MPGN. Using a refined two-step hemolytic assay, we measured the stability of CP convertases directly in the serum of 52 patients and 17 healthy controls. In four patients, CP convertase activity was prolonged compared to healthy controls, i.e. the enzymatic complex was stabilized. In three patients (2 C3G, 1 IC-MPGN) the convertase stabilization was caused by immunoglobulins, indicating the presence of autoantibodies named C4 nephritic factors (C4NeFs). Importantly, the assay also enabled detection of non-immunoglobulin-mediated stabilization of the CP convertase in one patient with C3G. Prolonged CP convertase activity coincided with C3NeF activity in all patients and for up to 70 months of observation. Crucially, experiments with C3-depleted serum showed that C4NeFs stabilized the CP C3 convertase (C4bC2a), that does not contain C3NeF epitopes. All patients with prolonged CP convertase activity showed clear signs of complement activation, i.e. lowered C3 and C5 levels and elevated levels of C3d, C3bc, C3bBbP, and C5b-9. In conclusion, this work provides new insights into the diverse aspects and (non-)immunoglobulin nature of factors causing CP convertase overactivity in C3G/IC-MPGN.